Sekolah Unggulan Tuntutan Pendidikan Global - Syuhud Syuhud (Bidayatuna, 2019)
The development of the world of education is very fast and competitive, the global world has contributed a lot to the direction of change in the education world, including in Indonesia. This change requires every educational institution to keep pace with the times in dynamic changes and competition, educational institutions that are able to show their superiority will be able to enter in this competition. The superior school which is the dream of all circles and groups should have clear terminology that can be understood by everyone, so that the word "superior" does not become the intellectual superiority of some people. In some developed countries, to indicate a good school it does not use the word “excellent” but uses the term “effective” and so on, in terms of the size of the content of superior schools in Indonesia it also does not meet the requirements. Top schools in Indonesia only measure part of their academic ability. In the real concept, a superior school is a school that continuously improves its performance and uses its resources optimally to develop overall student achievement.